THE IMPLEMENTATION OF REMEDIAL TEACHING IN SMA KEJAYAAN INDONESIA BINJAI - Rehlitna Situmorang; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study was aimed at finding out the implementation of remedial teachingincluded preparation, implementation of activities (process), and follow-up inSMA Kejayaan Indonesia Binjai for grade XI done by the English teacher.Another aim of this research was to find out the factor that contributed to thestudents’ success in remedial teaching. Descriptive qualitative research designwas used in this research. The participants of this study were an English teacherand 6 remedial students who had passed remedial teaching. The data sources inthis study were the teacher’s utterances and questionnaire answer sheets. The datawere collected by interviewing the teacher and spreading Google Formquestionnaire for the remedial students. Based on the interview, it was found thatthe teacher included preparation as to diagnose students’ difficulty,implementation as to re-explain the material, and follow up as to give thesuccessful students more motivation. It was concluded that what the teacher haddone can be called as remedial teaching because she had already done 6 out of 7steps of proper remedial teaching which are reviewing the case, selectingalternative action, provision of special services, implementing remedial teaching,re-measuring learning outcomes, and re-evaluating. For the questionnaire result,the factor that contributed to the students’ success in remedial teaching came frominternal and external factor.